1973
DOI: 10.1099/00221287-77-2-513
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Discontinuous Methanol Addition on the Growth of a Carbon-limited Culture of Pseudomonas

Abstract: S U M M A R YAs the interval between methanol additions to methanol-limited cultures of Pseudomonas methylotropha was increased beyond 20 s the yield of bacterial dry wt/g of methanol fell significantly. Discontinuous methanol additions also caused cycling in the values of a number of parameters, including pH, dissolved oxygen tension, CO, production and amino acid pool concentration. It is suggested that after each addition of methanol a burst of growth occurred, followed by a period of starvation. These obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Lowered yields of Artlmbactrr g1ohifomii.s at dilution rates below 0.1 h-l under carbon limitation thus cannot be attributed to the mode of substrate addition; the suggestion that the effect is caused by a maintenance energy requirement remains more plausible. Brooks & Meers (1973) have shown that growth can be affected by the discontinuous addition of substrate, so it would be wise to remember this in designing a continuous culture system, though their results do not have such wide-reaching implications as was initially thought. This is a paper of the Journal Series, New Jersey Agricultural Experiment Station, Cook College, Rutgers University, New Brunswick, New Jersey, U.S.A.…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lowered yields of Artlmbactrr g1ohifomii.s at dilution rates below 0.1 h-l under carbon limitation thus cannot be attributed to the mode of substrate addition; the suggestion that the effect is caused by a maintenance energy requirement remains more plausible. Brooks & Meers (1973) have shown that growth can be affected by the discontinuous addition of substrate, so it would be wise to remember this in designing a continuous culture system, though their results do not have such wide-reaching implications as was initially thought. This is a paper of the Journal Series, New Jersey Agricultural Experiment Station, Cook College, Rutgers University, New Brunswick, New Jersey, U.S.A.…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%
“…g Herbert, 1959Herbert, , 1961. This has usually been attributed to ii maintenance energy requirement, but Brooks & Meers ( 1973) suggested another possible cause.…”
Section: N T R O D U C T I O Nmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, it could be shown that overflow metabolites occur due to locally high substrate concentrations. Furthermore, short-term oxygen limitations of the microorganisms could be detected, causing a reduction of biomass and product concentration or the formation of overflow metabolites [14,20,23,25,26,28,30,31,33]. However, also positive effects of short-term oxygen limitation could be noticed as glucose is in excess and, thus, the number of dead cells decreased [14,26].…”
Section: Introductionmentioning
confidence: 95%
“…In contrast, cells are retained in their regions exist simultaneously within the same bioreactor. Studies investigating heterogeneities of nutrients by applying glucose pulse experiments or bioreactors with poor mixed regions were conducted with Saccharomyces cerevisiae [20][21][22][23], Escherichia coli [24][25][26][27] and other bacteria [28][29][30][31][32] and yeast. In these studies, it could be shown that overflow metabolites occur due to locally high substrate concentrations.…”
Section: Introductionmentioning
confidence: 99%